(Sor)ridere al tempo del COVID 19 (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Ironia 2.0: la vignetta in tempo di pandemia - 2. Satira vs libertà religiosa? - 3. Gioia e umorismo virtù anche cristiane - 4. Nota conclusiva.Smiling and laughing during pandemic timeABSTRACT: Are smiling and laughing ethically acceptable in times of Covid-Crisis? The paper tries to suggest an answer by taking into account a selection of comic strips posted on the WEB during the pandemic. The issue is addressed through two major points of view: the balance between the freedom of religion and the freedom of expression and the (possible) expressions of humor in the religious - particularly in the Catholic - tradition.